The role of IL-11 in chronic diseases - Zhang, Jingxuan; Leng, Yan; Li, Wenyuan; Wang, Bihan; Yang, Baichuan; Li, Wei (Frontiers in Immunology, 2026)
BackgroundInitially recognized for its role in hematopoiesis, Interleukin-11 (IL-11) is now understood to possess a wide spectrum of biological activities. It is involved in critical physiological processes, including immune cell differentiation, inflammatory response regulation, and tissue repair. Consequently, IL-11 is strongly implicated in the pathogenesis and progression of various chronic diseases.DiscussionThis review examines the multifaceted biology of IL-11, detailing its discovery, molecular structure, and signaling mechanisms. We also explore its expression patterns across different tissues. A primary focus is placed on elucidating the critical role of IL-11 in the pathogenesis and progression of various chronic diseases. Furthermore, we discuss the emerging therapeutic potential of targeting the IL-11 pathway, evaluating evidence from both experimental models and clinical studies.ConclusionBy synthesizing current knowledge on the biological characteristics and disease associations of IL-11, this review aims to provide a comprehensive theoretical foundation for future research into its role in chronic diseases and its potential as a therapeutic target.